Government expenditure and unemployment nexus in nigeria: a vecm approach - ADEJAYAN Ganiyu Kehinde; FASORANTI Modupe Mary; KOLEDOYE Emmanuel Sunday, (International Journal of Economic Performance (IJEP), 2026)
The public is scrutinizing and looking at the current unemployment rate in Nigeria despite the government's increased spending. Therefore, this study examined the relationships between government spending and unemployment in Nigeria from 1991 to 2020. The stationarity test was conducted using the Augmented Dickey-Fuller (ADF) test, and the long-term link between the variables was confirmed using Johansen co-integration. The unit root test revealed that the study's variables were stationary at the 5% level of significance, and the bound co-integration test confirmed a long-term relationship between the variables. The Vector Error Correction Model (VECM) was used to analyze the parameters of the study's variables. The finding confirmed capital expenditure (CEX) has a direct and non-significant relationship with unemployment rate (UEM) with absolute t-statistic of 0.61600 and t-value of t0.1= 1.697 for lagged one period; while, lagged two of CEX was significant and directly related to unemployment rate (UEM). The non-significant nature of the lagged one of capital expenditure (CEX) could be attributed to the fact that most of the funds assigned for capital expenditure are not often used effectively for capital projects; hence, worsen the rate of non-engagement of economic active age within the country. Therefore, government must channel its spending to capital project and not solely rely on price stability as a means to reduce unemployment within the economy.